2011
DOI: 10.1097/yct.0b013e31822145bd
|View full text |Cite
|
Sign up to set email alerts
|

QT Dispersion and Rate-Corrected QT Dispersion During Electroconvulsive Therapy in Elderly Patients

Abstract: The QTc interval, QTD, and QTcD may be higher than the normal limits before anesthesia in patients with major depression. The QTD and QTcD in the elderly, which are associated with increased risks of ventricular arrhythmias, are higher than those of the younger patients after electrical stimulus during ECT. Electrical stimulus may induce further increased risks of cardiac events in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A QTc greater than 500 ms has been reported to be highly abnormal for both men and women by guidelines provided by the Food and Drug Administration in 2012 . Moreover, QTc has been reported to possibly change dramatically and rapidly (i.e., within minutes) during ECT . Thus, QTc should be monitored with high time resolution to detect the high‐risk period (i.e., periods when QTc increases by more than 500 ms) to prevent fatal arrhythmia during ECT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A QTc greater than 500 ms has been reported to be highly abnormal for both men and women by guidelines provided by the Food and Drug Administration in 2012 . Moreover, QTc has been reported to possibly change dramatically and rapidly (i.e., within minutes) during ECT . Thus, QTc should be monitored with high time resolution to detect the high‐risk period (i.e., periods when QTc increases by more than 500 ms) to prevent fatal arrhythmia during ECT.…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, QTc has been reported to possibly change dramatically and rapidly (i.e., within minutes) during ECT. [3][4][5][35][36][37] Thus, QTc should be monitored with high time resolution to detect the high-risk period (i.e., periods when QTc increases by more than 500 ms) to prevent fatal arrhythmia during ECT. However, no such studies exist to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] In addition, nonpharmacological modalities, such as ECT and vagus nerve stimulation, can trigger arrhythmias by affecting the QT interval or causing heart block. 39,40 To avoid this confounding factor, patients who were treated for depression were excluded from our study. Similar to previous studies, we confirmed that older age is an independent risk factor for postoperative arrhythmia and that there was no positive association between depression and arrhythmia in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…34 Each option or their combination can potentially affect the incidence of arrhythmia in rather unpredictable ways. Antidepressants, ECT, and vagus nerve stimulation have possible arrhythmogenic effects, [35][36][37][38][39][40] yet, psychotherapy, such as biofeedback 41 and cognitive behaviour therapy, 42 can decrease the incidence of arrhythmia in cardiac patients.…”
Section: Résumémentioning
confidence: 99%
“…Many elderly patients may have cardiovascular complications and potential QT interval abnormalities caused by antidepressants. Moreover, increases in QTD and QTcD during elective surgery [29] and pharmacological sensitivities to remifentanil are more frequent in the elderly than in younger patients [30]. Therefore, the association between age and the effects of remifentanil should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%